Rethinking the Right to Education: Toward A Sociological Analysis - (:unkn) unknown (ISTANBUL UNIV, FAC LETTERS, DEPT SOCIOLOGY, 2015)
The neoliberalization process and increasing inequalities between and within the countries have created a deteriorating environment for the enjoyment of human rights especially for the working classes and other disadvantaged groups all around the world. This article seeks to contribute to the burgeoning field of sociology of human rights through providing a political economy analysis of the right to education within the context of neoliberal socio-economic conditions. It will be argued that economic, social and cultural rights, despite their formal recognition, have been demoted to 'consumer rights' with the increasing retreat of the state from the provision of the public services and the introduction of the market relations in these services since the mid-1970s. The purpose of this article is to explore the gap in formal recognition and substantive enjoyment of the right to education and to discuss the contributions of a sociological analysis for the realisation of this right.
Keywords: Sociology of the Right to Education; Educational Policy; Neoliberalism; Political Economy